Imago exegetica: visual images as exegetical instruments, 1400 - 1700 - Melion, Walter S. (Intersections, 2014)
This volume of 'Intersections: Interdisciplinary Studies in Early Modern Culture', consists of essays that pose fundamental questions about the relation between verbal and visual hermeneutics, especially as relates to biblical culture. Exegesis, as theologians and historians of art, religion, and literature, have come increasingly to acknowledge, was neither solely textual nor aniconic; on the contrary, following from Scripture itself, which is replete with verbal images and rhetorical figures, exegesis has traditionally utilized visual devices of all kinds. In turn, visual exegesis, since it concerns the most authoritative of texts, supplied a template for the interpretation of other kinds of significant text by means of images. Seen in this light, exegetical images prove crucial to understanding how meaning was constituted visually, not only in the sacred sphere but also in the secular.00
Literaturangaben
Keywords: Bible -- Hermeneutics; Bible -- Criticism, interpretation, etc; Bible -- Illustrations; Geschichte 1400-1700; Europe -- Religious life and customs; Europe -- Intellectual life; Konferenzschrift -- 2012 -- Atlanta, Ga.; Exegese; Hermeneutik; Ikonografie; Bibel; Bildersprache; Visuelle Kommunikation; Visualisierung